2016
DOI: 10.1007/s40069-016-0164-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wall Thickness on Thermal Behaviors of RC Walls Under Fire Conditions

Abstract: The objective of this paper is to investigate the effect of thickness and moisture on temperature distributions of reinforced concrete walls under fire conditions. Toward this goal, the first three wall specimens having different thicknesses are heated for 2 h according to ISO standard heating curve and the temperature distribution through the wall thickness is measured. Since the thermal behavior of the tested walls is influenced by thickness, as well as moisture content, three additional walls are prepared a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 12 publications
(11 reference statements)
1
5
0
Order By: Relevance
“…Grain heating time to reach the target temperature of 50 o C is approximately 80 minutes. Interestingly, the temperature profile of the grain bulk is similar to the thermal behavior of reinforced concrete walls after fire exposure in another study (Kang et al, 2016). In the present work, the grain bulk center had much lower temperatures than the peripheral of the grains near the source of the heating coils.…”
Section: -Hopper Heating Profilesupporting
confidence: 83%
“…Grain heating time to reach the target temperature of 50 o C is approximately 80 minutes. Interestingly, the temperature profile of the grain bulk is similar to the thermal behavior of reinforced concrete walls after fire exposure in another study (Kang et al, 2016). In the present work, the grain bulk center had much lower temperatures than the peripheral of the grains near the source of the heating coils.…”
Section: -Hopper Heating Profilesupporting
confidence: 83%
“…Shah et al (2017) reported the vulnerability of thin elements like slabs whose concrete will spall in post-earthquake fire events, resulting in the melting of reinforcement. Kang et al (2016) reported that the experimental results clearly showed that the temperature measured close to the exposed surface was higher in the thicker walls than that measured at the same location of the thinner walls. This is because the moisture clog inside thick walls with 200 mm and 250 mm thicknesses prevents heat transfer and acts as insulation.…”
Section: Literature Reviewmentioning
confidence: 89%
“…Different reinforcement configurations with different faces of fire exposure studies give a better understanding of their behavior (Song et al , 2019). Cross-section of the member, cover thickness and material quality also play a significant role in the thermal behavior of members (Kang et al , 2016; El-Hawary et al , 1997). The different loading circumstances on the column under temperature effects give different bending behavior (Raut and Kodur, 2011).…”
Section: Reinforced Concrete Elementsmentioning
confidence: 99%